Instructive problems of medium diﬃculty in math enviroments of Lithuania - Kašuba, Romualdas (Lietuvos matematikos rinkinys, 2018)
In the paper an attempt to represent some not too easy and in the same time not diﬃcult, accessible, useful and challenging problems used in Lithuanian math events, as well as in training high-scool and University students, is undertaken.
Keywords: Metaphoricalness of problem formulations; their digital attractiveness; emotional suggesti-veness of natural conditions; psychological steps of solution; heuristic strategies and levels of compre-hending